INTERNET ADDICTION AMONG ADOLESCENTS IN A WESTERN BRAZILIAN AMAZONIAN CITY - Tatiane Dalamaria; Wagner de Jesus Pinto; Edson dos Santos Farias; Orivaldo Florencio de Souza (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: Analyze the prevalence and factors associated with internet addiction in a sample of high school adolescents in Acre, a state in northern Brazil. Methods: A population-based cross-sectional study was conducted with 1,387 adolescents between 14 and 18 years old enrolled in high schools in the city of Rio Branco, Acre. A structured questionnaire with questions about demographics, family and behavioral patterns was applied. Internet addiction was verified using the Internet Addiction Test (IAT), with a cutoff equal to or greater than 70 points. The associated factors were identified by multiple logistic regression analyses. Results: The overall prevalence of Internet addiction was 10.6%. Higher dependence was observed in females. The factors associated with Internet addiction were being female, using the computer for more than two hours a day during weekdays and on the weekend, not practicing physical activities and going out to dance at nightclubs and concerts at least once a month. A protective association of reading habits in relation to Internet dependence was observed. Conclusions: The present study showed a high prevalence of Internet dependence, with female adolescents being more susceptible. Behavioral aspects were associated with internet dependence in a sample of adolescents from Rio Branco, Acre.